2015
DOI: 10.1007/s11999-014-3870-9
|View full text |Cite
|
Sign up to set email alerts
|

Has the Incidence of Thoracolumbar Spine Injuries Increased in the United States From 1998 to 2011?

Abstract: Background While most motor vehicle crash (MVC)-related injuries have been decreasing, one study showed increases in MVC-related spinal fractures from 1994 to 2002 in Wisconsin. To our knowledge, no studies evaluating nationwide trends of MVC-related thoracolumbar spine injuries have been published. Such fractures can cause pain, loss of functionality or even death. If the incidence of such injuries is increasing, it may provide a motive for reassessment of current vehicle safety design. Questions/purposes We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 11 publications
(18 reference statements)
2
22
0
1
Order By: Relevance
“…1 The same trend has been observed with increasing incidence between 2001 and 2007 in China. Motor vehicle accidents are the leading cause of spinal trauma followed by falls from a height.…”
Section: Introductionsupporting
confidence: 58%
“…1 The same trend has been observed with increasing incidence between 2001 and 2007 in China. Motor vehicle accidents are the leading cause of spinal trauma followed by falls from a height.…”
Section: Introductionsupporting
confidence: 58%
“…32 Indeed, Doud et al showed increases in the rate of thoracolumbar injury incidence across the nation from 1998 to 2011. 33 The improved automotive safety measures combined with the aggressive use of surveillance imaging techniques seem responsible for this paradoxical trend. 34,35 Moreover, more previously fatal injuries are perhaps reaching the emergency room now than in previous decades.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracolumbar vertebral fractures in young adults are common and are often associated with profound social consequences. Most of these primarily affect males and result from motor accidents and falls from heights, which are associated with high kinetic energy 6 . The intervertebral disc is a cartilage complex that is vulnerable to injury from stretches or shear force, whereas great compression forces can also result in traumatic intervertebral disc injuries 7 .…”
Section: Discussionmentioning
confidence: 99%